Pengaruh Tunjangan Kesejahteraan terhadap Produktivitas Kerja Karyawan pada Rumah Sakit Jasa Kartini - Samsu Hendriatna (LP2M Universitas Perjuangan Tasikmalaya, 2019)
The objectives of this research are to determine and analyze the influence of welfare benefits, education and training on work productivity at Rumah Sakit Jasa Kartini Tasikmalaya. The used method in this research is survey methods and technique of data collection is done by 1) interview and questionnaires to obtain primary data, and 2) Study the documentation to obtain secondary data. Data analyses in this research use the multiple linier regression analyses by using SPSS software. The results of this research show that there is a significant influence of welfare benefits, education and training, simultaneously, to work productivity at Rumah Sakit Jasa Kartini Tasikmalaya. There is a significant influence of welfare benefits, partially, to work productivity at Rumah Sakit Jasa Kartini Tasikmalaya. There is a significant influence of education, partially, to work productivity at Rumah Sakit Jasa Kartini Tasikmalaya. There is a significant influence of training, partially, to work productivity at Rumah Sakit Jasa Kartini Tasikmalaya.